Representation of Young People in British Films Set in Coastal Resorts - Mazierska, Ewa (Hungarian Journal of English and American Studies, 2021)
This article examines representations of young people in three recent films set in British seaside resorts: Jellyfish (2018), directed by James Gardner Vs. (2018), directed by Ed Lilly, and Eaten by Lions (2018), directed by Jason Wingard, in light of the fact that in the past few decades resorts have been seen as places from which young people try to escape, rather than go to.  My essay shows how the experience of those who visit the resorts is different from that of those who live there. It considers the production values, characters, stories, and locations of these films, drawing on secondary research on coastal resorts and their cinematic representations, Erving Goffman’s taxonomy of spaces into “front” and “back regions,” and Mikhail Bakhtin’s concept of the carnivalesque. The article also links the representation of the resort itself to wider discourses about England, class, and race. (EM)